Transcriptional profiling of Gram‐positive Arthrobacter in the phyllosphere: induction of pollutant degradation genes by natural plant phenolic compounds. (23rd January 2014) - Scheublin, Tanja R.; Deusch, Simon; Moreno‐Forero, Silvia K.; Müller, Jochen A.; van der Meer, Jan Roelof; Leveau, Johan H. J.
Summary A rthrobacter chlorophenolicus A6 is a Gram‐positive, 4‐chlorophenol‐degrading soil bacterium that was recently shown to be an effective colonizer of plant leaf surfaces. The genetic basis for this phyllosphere competency is unknown. In this paper, we describe the genome‐wide expression profile of A. chlorophenolicus on leaves of common bean (Phaseolus vulgaris) compared with growth on agar surfaces. In phyllosphere‐grown cells, we found elevated expression of several genes known to contribute to epiphytic fitness, for example those involved in nutrient acquisition, attachment, stress response and horizontal gene transfer. A surprising result was the leaf‐induced expression of a subset of the so‐called cph genes for the degradation of 4‐chlorophenol. This subset encodes the conversion of the phenolic compound hydroquinone to 3‐oxoadipate, and was shown to be induced not only by 4‐chlorophenol but also hydroquinone, its glycosylated derivative arbutin, and phenol. Small amounts of hydroquinone, but not arbutin or phenol, were detected in leaf surface washes of P. vulgaris by gas chromatography‐mass spectrometry. Our findings illustrate the utility of genomics approaches for exploration and improved understanding of a microbial habitat. Also, they highlight the potential for phyllosphere‐based priming of bacteria to stimulate pollutant degradation, which holds promise for the application of phylloremediation.